Sabellidae (Annelida) from the Faro coastal lake (Messina, Ionian Sea), with the first record of the invasive species Branchiomma bairdi along the Italian coast - GIANGRANDE, A.; COSENTINO, A.; LO PRESTI, C.; LICCIANO, M. (Mediterranean Marine Science, 2012)
In the present paper, morphological and ecological observations on 4 sabellid taxa, Branchiomma bairdi, B. luctuosum, Megalomma lanigera and Myxicola sp., collected from the coastal lake of Faro (Messina, Ionian Sea) (26-36 psu), are reported. Megalomma lanigera, Myxicola sp. and B. luctuosum were collected from the soft bottom in shallow water and B. bairdi from the hard bottom of an internal channel. The presence of the latter is remarkable, as there is no previous record of this species along the Italian coast, and it confirms the lake of Faro as a very favourable environment for the introduction of alien species, which has occurred frequently as a result of aquaculture. High intraspecific variation was observed for M. lanigera, whilst more extensive analysis is required to ascertain the taxonomic status of the Myxicola specimens, including a review of all Mediterranean data currently attributed to M. infundibulum.